The experimental study and numerical simulation of falling liquid film flow on horizontal tubes - Hassan, Ibnu Anas (2017)
This research is motivated by two observations: No report has been found so far in studies of water falling film up to 100 mm intertube spacing. No simulation analysis of film thickness under influence of intertube spacing in 3 dimensional models. Therefore, to the best of author’s knowledge, this research aims to illuminate the effects of intertube spacing between horizontal tubes on water falling film. An experimental investigation of water falling film temperature was conducted to explore the characteristics of heat transfer coefficients. In this study, the intertube spacing from smallest size of 8 mm and up to 100 mm were analyzed for Reynolds number range of 300 to 3300. The experimental data was extracted from calibrated test rig and the effect is investigated using numerical study. On the other hand, the effect of film thickness is numerically investigated for intertube spacing range of 10 mm to 40 mm. The numerical simulation was presented using the Volume of Fluid (VOF) technique where it is capable in determining temperatures and thickness of water falling film under influence of ambient factors. The experimental results reveal that intertube spacing of 133 mm produced the maximum heat transfer coefficient of 6 kW/m² K with percentage of error below 7%. The results of the numerical simulation indicate that the 40 mm intertube spacing presented the minimal average film thickness of 0.3 mm within ± 50% errors. Implications of the results and future research directions are also presented.